SERANGGA PREDATOR PADA EKOSISTEM PADI SAWAH DI KECAMATAN TOMBATU, KABUPATEN MINAHASA TENGGARA - Herianto I. Kojong; Moulwy F. Dien; Noni N. Wantah (Universitas Sam Ratulangi, 2015)
ABSTRACTThe study aims to determine the type and predators of insect populations in lowlandrice ecosystems in the district Tombatu Southeast Minahasa regency. The experimentwas conducted on the rice in the village Tombatu, District Tombatu, SoutheastMinahasa Regency. The research carried out by the survey on rice crops in the districtTombatu Southeast Minahasa District, the Village Tombatu One, Tombatu Two, andThree Tombatu. Sampling was carried out with a diagonal slice method thatestablishes five sub-plot that is on the corner and the middle of the sampling sites.Sampling was performed using insect nets swung over rice plant as much as ten timesthe double swing. Insects are netted immediately put into